2021
DOI: 10.1002/ird.2589
|View full text |Cite
|
Sign up to set email alerts
|

Country report Indonesia

Abstract: As the fifth most populated country in the world, Indonesia has been facing huge challenges in food security. With a growing population and a more competitive environment, these challenges will only increase in the future. Climate change has put more pressure on the agricultural sector. These conditions will make farmers more vulnerable to poverty in light of their present relatively low standard of living. Under these circumstances, high‐level attention on the part of all stakeholders is needed currently as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Improvement and development of irrigation infrastructure are crucial for Indonesia since there are still many water limitations and shortages in several agricultural areas (Hadi Darwanto 1999). Public-private cooperation is needed to accelerate improving and development of irrigation infrastructures in Indonesia (Idris 2021). Despite the crucial need for irrigation facilities and management improvements to reduce the impacts of salinity (Karolinoerita and Annisa 2020;Yan et al 2021), research and studies in this area still need to be done as indicated by the limited scientific documentation and literature.…”
Section: H Challenge In Reducing the Negative Impacts Of Salinity Due...mentioning
confidence: 99%
“…Improvement and development of irrigation infrastructure are crucial for Indonesia since there are still many water limitations and shortages in several agricultural areas (Hadi Darwanto 1999). Public-private cooperation is needed to accelerate improving and development of irrigation infrastructures in Indonesia (Idris 2021). Despite the crucial need for irrigation facilities and management improvements to reduce the impacts of salinity (Karolinoerita and Annisa 2020;Yan et al 2021), research and studies in this area still need to be done as indicated by the limited scientific documentation and literature.…”
Section: H Challenge In Reducing the Negative Impacts Of Salinity Due...mentioning
confidence: 99%
“…The impact of Covid-19 has further highlighted the need for sustainable development programs to address poverty and promote a green economy [12]. Indonesia's economic growth is closely linked to social and economic conditions, with regions such as North Sulawesi, Riau, and Bali demonstrating optimal economic growth values [13]. To comprehensively address these challenges, Indonesia must address human capital issues, geographical disparities, and low productivity, as well as prepare for shocks such as those resulting from climate change [14].…”
Section: Introductionmentioning
confidence: 99%